Optimal Spatial Distribution of Gasoline Stations in Baghdad Province Utilizing GIS Techniques - H. Mahmood, Faleh; H. Shaban, Auday; A. Numan, Sadic (Iraqi Journal of Science, 2023)
Studying the spatially distribution pattern of fuel station in province of Baghdadwas done by utilizing GIS techniques which they are the most powerful tools fordesign, display and analysis for the spatial data. Nearest Neighbor Analysis methodwas applied for analyzing the spatial distributions of the fuel stations. Baghdad wasconsidered to be divided in to two main parts (outskirts of Baghdad and center ofBaghdad). The nearest neighbour for all parts of Baghdad indicates for thedistribution pattern is random and differs from place to another in randomly rate.